2019
DOI: 10.3390/mti3020023
|View full text |Cite
|
Sign up to set email alerts
|

Tango vs. HoloLens: A Comparison of Collaborative Indoor AR Visualisations Using Hand-Held and Hands-Free Devices

Abstract: In this article, we compare a Google Tango tablet with the Microsoft HoloLens smartglasses in the context of the visualisation and interaction with Building Information Modeling data. A user test was conducted where 16 participants solved four tasks, two for each device, in small teams of two. Two aspects are analysed in the user test: the visualisation of interior designs and the visualisation of Building Information Modeling data. The results show that the Tango tablet is surprisingly preferred by most users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…However, they also found that there were no differences between HMDs and tablets for dynamic tasks, in which users had to physically move during task execution. Likewise, Riedlinger et al [41] found that users preferred tablet devices over HMDs for cooperative interior design tasks. Therefore, while it may seem obvious that HMDs should be favoured over mobile phones, there is a need for evidence that this is true for different domains and tasks.…”
Section: Remote Work Support Using Head Mounted Devicesmentioning
confidence: 99%
“…However, they also found that there were no differences between HMDs and tablets for dynamic tasks, in which users had to physically move during task execution. Likewise, Riedlinger et al [41] found that users preferred tablet devices over HMDs for cooperative interior design tasks. Therefore, while it may seem obvious that HMDs should be favoured over mobile phones, there is a need for evidence that this is true for different domains and tasks.…”
Section: Remote Work Support Using Head Mounted Devicesmentioning
confidence: 99%
“…In the second stage, the subfields in which smart glasses were employed and the corresponding ratios were analyzed (Figure 6). The computer science field is developing HCI [18][19][20][21][22][23] as an interaction technology between humans and computers; object recognition [24,25], which is a technology that recognizes what the user sees, based on a camera; and visualization [8,26,27] to visually show data to users (Table 1). There are several research cases in the field of visualiza-tion.…”
Section: Smart Glasses Research Trendmentioning
confidence: 99%
“…Several studies have been conducted on GUI [ 18 , 49 ] and NUI [ 13 , 20 , 67 ] with HoloLens. The GUI studies have primarily focused on the evaluation of the interface, while a NUI study placed significance on the design and prototype of the interface.…”
Section: Literature Reviewmentioning
confidence: 99%